Correction: Circumvention of common labelling artefacts using secondary nanobodies. Issue 48 (11th December 2020) - Sograte-Idrissi, Shama; Schlichthaerle, Thomas; Duque-Afonso, Carlos J.; Alevra, Mihai; Strauss, Sebastian; Moser, Tobias; Jungmann, Ralf; Rizzoli, Silvio O.; Opazo, Felipe
Abstract : Correction for 'Circumvention of common labelling artefacts using secondary nanobodies' by Shama Sograte-Idrissi et al., Nanoscale, 2020, 12, 10226–10239, DOI: ; 10.1039/D0NR00227E .